Mechanical properties of CAD-CAM blocks for base denture prosthesis after chemical disinfection protocols - Toala, Oscar Oswaldo Marcillo (2020)
The innovation of computerized procedures led to the manufacture of polymethylmethacrylate blocks (CAD/CAM PMMA blocks) for denture base, showing excellent mechanical and biological properties, better adaptation, and reduced number of attendances. However, disinfection protocols are necessary in order to remove the biofilm on the prosthetic surface. The effect of these disinfectants is widely discussed in the literature, showing several effects on the mechanical and surface properties of resins depending on the concentration, immersion time, and type of solution. The objective of this work was to evaluate the short and long term effect of disinfectant solutions on the mechanical and surface properties of CAD/CAM PMMA resin for denture base. The tested resins were VIPI Gum Block (CAD/CAM PMMA) (VIPI) and VIPI Cril Plus (Conventional PMMA) (VIPI) and the disinfectant solutions were: Control group: Deionized water; H1 = 1% sodium hypochlorite; H05 = 0.5% sodium hypochlorite; and C2 = 2% chlorhexidine gluconate. One hundred and forty specimens were made (12x12x3mm) for microhardness (KHN) and roughness (Ra) tests (n = 10); and 280 specimens (65x10x3 mm), for Flexural Strength (FS) and Flexural Modulus (FM) (n = 10). Each disinfection cycle represented a 10 minutes immersion in each solution and the evaluated times were: 0 (initial), 14, 30, 130 and 260 cycles. The statistical tests for KHN and Ra were repeated-measures ANOVA and, subsequently, the Tukey HSD test with a significance level of 5%. For FS and FM, the statistics used was 3-Way ANOVA and Tukey\'s test for multiple comparisons, adopting a significance level of 5%. The first work evaluated the short-term effect of disinfectant solutions on the surface properties of the resin. The Ra test showed no significant difference in resins when exposed to the solutions during the evaluated period (p> 0.05). However, the KHN test showed that CAD/CAM PMMA was superior to conventional when immersed in all solutions (p <0.05) at all times (p <0.05). The second article evaluated a long-term effect of CAD/CAM PMMA resin immersed in the solutions. In surface properties, KHN showed a significant difference in the type of resin (p <0.000), time (p = 0.002) and the solution * resin interaction (p <0.000). The Ra showed a significant difference in the type of solution (p = 0.007). In RF, the resin was decisive in the result in Mpa (p = 0.001), the time was another relevant factor (p = 0.032), and the solution*resin interaction (p = 0.008). In the ME, the relevant factors were: resin (p = 0.001), time (p = 0.032), and solution * resin (p = 0.008). The CAD/CAM PMMA resin showed higher initial values in KHN and FS, Ra and FM similar to the conventional PMMA resin. However, the greater the exposure (cycles) of the resin to disinfectant solutions, the KHN, FS and FM tests showed higher values of the conventional PMMA resin with a significant difference. Within the limitations of this study, the CAD/CAM PMMA resin showed favorable properties according to each experiment performed and the disinfectant solutions (H1, H05 and C2) did not negatively affect the resin over time.